XWand: UI for Intelligent Spaces - Wilson, Andy; Shafer, Steven (CHI '03 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2003)
The XWand is a novel wireless sensor package that enables styles of natural interaction with intelligent environments. For example, a user may point the wand at a device and control it using simple gestures. The XWand system leverages the intelligence of the environment to best determine the user's intention. We detail the hardware device, signal processing algorithms to recover position and orientation, gesture recognition techniques, a multimodal (wand and speech) computational architecture and a preliminary user study examining pointing performance under conditions of tracking availability and audio feedback.